Investigations into Chemical Looping Combustion and Three Reactor Chemical Looping for Hydrogen and Ammonia Production using Aspen Plus - Kappagantula, Ratnakumar Venkata (Curtin University, 2024)
Two chemical looping processes are investigated using Aspen Plus simulations in this thesis, namely Chemical Looping Combustion (CLC) and Three Reactor Chemical Looping (TRCL). Both hold the promise of obtaining energy from fossil fuels while delivering sequestration-ready CO2. Contributions include the first-time use of Aspen’s FluidBed reactor model for CLC, a new flowsheet for ammonia production using TRCL, and design of a 150-ton CLC boiler using multiple parallel reactors to replace an existing industrial boiler.